Interval Type 2 Fuzzy Logic Based Multifocus Image Fusion - Myna, AN; Prakash, J (International Journal of Computer Sciences and Engineering, 2025)
Multifocus image fusion is a process of obtaining one clear image using a set of images where some regions in each image are in focus and other regions are out of focus. Extracting the in-focus regions from the input images and fusing them together into a new image is a major task. There are various approaches used for this purpose. A novel approach based on Interval Type 2 Fuzzy Logic combined with discrete wavelet transform has been experimented and the results have been presented in this paper. Mamdani and Sugeno Type fuzzy logic systems have been tested and results are compared with Type 1 Fuzzy Logic systems. Better results are obtained for Type 2 Sugeno fuzzy logic system.